(3EOGQI GdGYdGf h GbJUGOjGJg (B/s - (3cGaj, eUWai jhSas ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2015)
(3GOGQI GdGYdGf (B- (3GdCgejI GdGbJUGOjI ddGYdGf (B- (3GdGYdGf aj GdCfXeI GdGbJUGOjI GdeNJdaI (B-(3hcGdGJ GdGYdGf (B-(3JfXje CLgRI GdGYdGf aj GdhSGFd GdGYdGfjI (B- (3GdHjFI GdJShjbjI ef GdefXhQ GdGbJUGOj (B-(3WQb JMOjO GdeNUUGJ GdGYdGfjI (B- (3GdGYdGf h JSYjQ GdefJLGJ (B-(3bjGS h Jbjje aGYdjI GdGYdGf (B- (3LOhdI GdeNUUGJ GdGYdGfjIs
(3GdeQGLY U(B.261s
Keywords: (3GdGOGQIs; (3GdGYdGf GdJLGQjs